Cambridge Checkpoint Science Coursebook 9 - Jones, Mary; Sang, David (Cambridge : Cambridge University Press, 2013)
Written by well-respected authors, the Cambridge Checkpoint Science suite provides a comprehensive, structured resource which covers the full Cambridge Secondary 1 framework and seamlessly progresses into the next stage. This engaging course supports teaching of the Science framework both theoretically and practically, with full coverage of the Scientific Enquiry framework integrated throughout the series. This Coursebook for Stage 9 gives a thorough introduction to the concepts, and offers a wealth of ideas for hands-on activities to make the subject matter come to life. Integrated review of topics from Stages 7 and 8 as well as full coverage of the Stage 9 content provides preparation for the Cambridge Checkpoint Science test and a solid foundation for progression into the Cambridge IGCSE Sciences.